STABILITY OF CATFISH WASTE SILAGE (Pangasius hypophthalmus) DURING STORAGE AT ROOM TEMPERATURE - Aditya Rachman Aliunputra; Bustari Hasan; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractOne of the efficient and effective preservation methods is the addition of acid or silage (Hasan et al., 2001). This study aimed to evaluate the differences in the stability of the silage storage of catfish waste made with the addition of formic acid at pH 5 and pH 4. The method used in this research was experimental, with the addition of formic acid The results of pH and NPN analyzes were analyzed using paired T-test (paired samples test) with statistical software (SPSS) which then saw the significance value (p).until the silage reached pH 4 and pH 5 during storage for 21 days at room temperature. The parameters were physical character (colour and smell), pH analysis, NPN, proximate, and amino acids. The results showed that the addition of formic acid reached pH 4 and pH 5 significantly affected the pH stability value and the NPN value of catfish waste silage during storage at room temperature (± 29oC). The best treatment was the addition of formic acid to pH 4 on the 0th day as seen from the analysis of NPN and proximate (protein, fat, water, ash), with a brownish colour (does not change from the colour of catfish waste), has a sour aroma, pH value of 4, NPN 45.79%, protein 65.30 (% dw), fat 31.21 ( % dw), water 75.80 (% gw), ash 3.49 (% dw), and total amino acids 6.50%. Silage stability in the addition of formic acid to pH 4 and pH 5 during the storage period is relatively stable. Therefore, the addition of formic acid to the silage of catfish waste up to pH 5 is considered more efficient, has lower acidity so it is likely to be preferred as a feed mixture, and relatively cheaper because it uses less formic acid.Keywords: Fish guts, formic acid, pH, silage,  stability